Dolittle [videorecording (DVD)] - Gaghan, Stephen; Downey, Robert, Jr., 1965-; Banderas, Antonio; Sheen, Michael (Universal Pictures Home Entertainment, 2020)
After losing his wife seven years earlier, the eccentric Dr. John Dolittle, famed doctor and veterinarian of Queen Victoria's England, hides behind the walls of Dolittle Manor with only his menagerie of exotic animals for company. But when the young queen falls gravely ill, a reluctant Dolittle is forced to set sail on an epic adventure to a mythical island in search of a cure. The doctor is joined on his quest by a young, self-appointed apprentice and a raucous coterie of animal friends.